2005
DOI: 10.1111/j.1365-2109.2005.01259.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of cellulase and xylanase activity in freshwater crayfish and marine prawns

Abstract: Cellulase and xylanase digestive enzyme activities were compared in four freshwater crayfish (Genus Cherax) and three marine prawn (Genus Penaeus) species. Temperature and pH profiles for cellulase (endoglucanase) were found to be very similar in all species, with maximum activity occurring at 60°C and pH 5.0. Temperature and pH profiles for xylanase (endoxylanase) were also very similar in all crayfish species, with maximum activity occurring at 50°C and pH 5.0. Xylanase activity was not detected in the three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 22 publications
3
21
1
Order By: Relevance
“…In particular, decomposing cellulose and structural polysaccharides generally requires multiple enzymes (Watanabe and Tokuda, 2001), which makes analyzing enzyme activities more difficult. In addition, most such studies on invertebrates have used homogenates of digestive organs such as the digestive gland, stomach or intestine as enzyme samples (Gianfreda et al, 1979;Teo and Sabapathy, 1990;Crawford et al, 2005), but the effect of reaction product conversion to other substances by metabolic enzymes existing in such organs should not be neglected. For this reason, determining substrate reduction seems to be the best way to quantify digestive enzyme activity, but for polysaccharide-degrading enzymes such as cellulase, accurately determining substrate quantity is difficult because of limited methods.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, decomposing cellulose and structural polysaccharides generally requires multiple enzymes (Watanabe and Tokuda, 2001), which makes analyzing enzyme activities more difficult. In addition, most such studies on invertebrates have used homogenates of digestive organs such as the digestive gland, stomach or intestine as enzyme samples (Gianfreda et al, 1979;Teo and Sabapathy, 1990;Crawford et al, 2005), but the effect of reaction product conversion to other substances by metabolic enzymes existing in such organs should not be neglected. For this reason, determining substrate reduction seems to be the best way to quantify digestive enzyme activity, but for polysaccharide-degrading enzymes such as cellulase, accurately determining substrate quantity is difficult because of limited methods.…”
Section: Discussionmentioning
confidence: 99%
“…Xylanases from the marine sources can have some remarkable qualities with respect to stability at high temperature and pH, which needs attention. There are a few studies reported on marine xylanases (6)(7)(8)(9)(10)(11)(12)(13) and it is important to look into more potential xylanases from the marine sources. Recently, the interest in application of endoxylanases in the production of xylooligosaccharides from xylan sources is growing rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of proteinases, endo--1,4-glucanase, -1,4-glucanase, xylanase, lichenase and, laminarinase has been documented previously in Cherax species (Crawford et al 2005;Figueiredo et al 2001). CrayWsh of the genus Cherax are omnivorous consuming mainly plant material and clearly their digestive enzyme complement correlates well with the substrates that they would encounter in their natural diet.…”
Section: Digestive Enzymesmentioning
confidence: 99%
“…Like laminarinase, these enzymes may be widely distributed throughout the Crustacea. However they may only be present in species that encounter these substrates in their diet (Crawford et al 2005).…”
Section: Digestive Enzymesmentioning
confidence: 99%
See 1 more Smart Citation